2015
DOI: 10.19026/ajfst.7.1736
|View full text |Cite
|
Sign up to set email alerts
|

The Extraction and Properties of <em>Carica papaya</em> Seed Oil

Su N2,
et al.

Abstract: The main objective of the present study was to evaluate the suitability of Ultrasound-Microwave synergistic Extraction (UMAE) for the recovery of papaya seed oil as compared to Ultrasound-Assisted Extraction (UAE). The efficiency of these two methods was assessed by comparing the physicochemical properties and oxidative stability of papaya seed oil. The analytic tests were color, unsaponifiable matters, iodine value, acid value and peroxide value. The fatty acid components were analyzed by GC. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…On the other hand, the SFE with neat CO 2 at 20 and 30 MPa allowed to obtain low polarity extracts with yields between 18.80 and 20.59%. Previously, reports showed that papaya seeds are a source of low polarity extracts; da Silva and Jorge (2017) reported oil content in papaya seeds above 20%, while Li et al (2015) recovered oil with yields between 22 and 26% by ultrasound assisted extraction. In these studies, a high content of polyunsaturated fatty acids in oils (particularly linoleic acid) were observed, however, phenolic compounds were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the SFE with neat CO 2 at 20 and 30 MPa allowed to obtain low polarity extracts with yields between 18.80 and 20.59%. Previously, reports showed that papaya seeds are a source of low polarity extracts; da Silva and Jorge (2017) reported oil content in papaya seeds above 20%, while Li et al (2015) recovered oil with yields between 22 and 26% by ultrasound assisted extraction. In these studies, a high content of polyunsaturated fatty acids in oils (particularly linoleic acid) were observed, however, phenolic compounds were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hands, Li et al () compared the efficiency of ultrasound‐microwave synergistic solvent extraction (UMSSE) and UASE in extracting papaya seed oil. The UMSSE was performed using an ultrasonic horn transducer and a microwave oven, whereas the UASE was performed using an ultrasonic water bath.…”
Section: Papaya Seed Oil Extraction Methodsmentioning
confidence: 99%
“…It is used as a soap substitute that is able to remove stains. Papaya seeds are used to extract oil, and their yield could be up to 34 % [1,2]. Papaya seed oil is rich in oleic acid and triacylglycerol; its nutritional and functional properties are highly similar to olive oil [3].…”
Section: Introductionmentioning
confidence: 99%